Spacing and plant population for dry bean harvest mechanization - Horn, Fernando Luiz; Schuch, Luis Osmar Braga; Silveira, Expedito Paulo; Antunes, Irajá Ferreira; Vieira, José Cavalcante; Marchioro, Gelso; Medeiros, Dener Fábio; Schwengber, José Ernani (Pesquisa Agropecuaria Brasileira, 2000)
The experiment was conducted in 1992/93 season at Centro Agropecuário da Palma (CAP) of the Universidade Federal de Pelotas (UFPel), in Pelotas, Brazil, to evaluate the effect of spacing variations between rows and plant populations on agronomic characteristics related to mechanized harvest for dry bean (Phaseolus vulgaris L.). Three different row spacing (25, 50 and 75 cm) and four different plant populations/ha (100, 200, 350 and 500 thousand) were used, utilizing the cultivar Pampa, indeterminate growth habit type II as reagent. The field trial was in randomized blocks, with four replications. Positive interaction between factors was observed for the lodging index, where the increase in the plant population tended to reduce it. The combination of larger spacing with smaller plant population resulted in a higher lodging index. The reduction in the row spacings, in spite of reducing the plant height, the pod insertion height and the grain yield, resulted in an increase of the lowest pod tip height and in a reduction of the percentage of plants with pods touching the soil surface. The increase in the plant population, despite of not affecting the majority of the agronomic characteristics of the plant, resulted in a reduction of the percentage of plants with pods touching the soil and did not cause any alteration in the grain yield.